Ο ρόλος των επαγγελματιών υγείας στην προώθηση του οικογενειακού προγραμματισμού: μετα - σύνθεση - Γιάγκου, Παναγιώτα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Introduction: Τhe role of health professionals providing advice on family planning is particularly important and useful. Informed people with necessary knowledge about their sexual and reproductive health are more responsible in their decisions. , Aim: The aim of this metasynthesis was to investigate the role of health professionals in promoting family planning. Material and Method: The method used was meta-synthesis. We searched the relevant English and Greek bibliography in the databases COCHRANE, CINAHL with key words: Contraceptive, Contraception, Midwives, Family Planning, Reproductive Health, and Qualitative Study, Sexual Health with all possible combinations. During the original search, 204 articles were selected, of which 8 were selected, which met the inclusion criteria. Results: In many countries, health professionals face many obstacles to provide advices for family planning. Health professional’s education and strategies used to promote family planning affected by stereotypes and prejudices. The best and most effective approach to promoting family planning is implemented in Sweden. Conclusion: Family planning and contraceptive counseling are important part of the role of many health professionals. However, in some countries there is inadequate education for health professionals for family planning.
Keywords: Contraceptive; Contraception; Midwives; Family planning; Reproductive health; Sexual health; Qualitative study